Efek Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Kartu Internet Telkomsel - Romadhoni, Buyung (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
This study aims to analyze the influence of product quality and price on Telkomsel internet card purchase decisions. In today's digital age, the need for fast, stable, and affordable internet services is increasing, so it is important for telecommunications service providers to understand the factors that influence consumer decisions. This study uses a quantitative approach with a survey method on a number of respondents using Telkomsel internet cards. The population in this study is Telkomsel internet card users in Makassar City. The sample in this study was 97 respondents. The results of the analysis show that product quality and price have a significant effect on purchasing decisions. Product quality that includes network speed, signal stability, and wide area coverage proves to be a key consideration in purchasing decisions. Meanwhile, competitive prices and in accordance with the benefits offered also contribute to shaping consumer preferences. This finding indicates that Telkomsel needs to continue to maintain the quality of its services while implementing the right pricing strategy to increase competitiveness and customer loyalty.